Prevalence of atrial fibrillation in intracerebral hemorrhage. (12th June 2013) - Horstmann, S.; Rizos, T.; Jenetzky, E.; Gumbinger, C.; Hacke, W.; Veltkamp, R.
<x xml:space="preserve">Abstract</x> Background and purpose Oral anticoagulation (OAC) is an effective preventive therapy for ischemic stroke in atrial fibrillation (AF). The management of anticoagulation in AF patients with previous intracerebral hemorrhage (ICH) is challenging. The aim of this study was to determine the prevalence of AF after acute ICH in a consecutive monocenter cohort, and to document the subsequent management with respect to OAC. Methods Consecutive patients with spontaneous ICH were prospectively included within 19 months. Diagnosis of AF was based on medical history, 12‐lead electrocardiogram (ECG), 24‐h and continuous ECG monitoring. CHADS2 scores and patient medication were recorded at admission and after 3 months. Additionally, after 3 months mortality, the management of anticoagulation and a newly detected AF were assessed. Results In total, 206 ICH patients were eligible for data analysis. After 3 months, AF had been diagnosed in 64/206 ICH patients (31.1%). Mortality after 3 months was higher in patients with AF in univariate analysis (45.3% vs. 31.0%). After adjusting for comorbidities and OAC use, AF did not remain an independent predictor for mortality. In total, 35 patients with AF survived 3 months. Of these, CHADS2 score was 2 (2/3, median, interquartile range (IQR)) and 27/35 patients had an indication for OAC with respect to the CHADS2 score, but only 25.7% had been (re‐)started on OAC. No consistent factors for deciding whether to initiate OAC treatment could be identified. Conclusions Atrial fibrillation is a frequent comorbidity in patients suffering an ICH. Our findings underline the prevailing uncertainty regarding the anticoagulation management of AF after ICH.